Penatalaksanaan Gagal Napas pada Poliautoimun Multipel Sklerosis dengan Krisis Miastenia - Octavia, Eva; Halimi, Radian Ahmad; Sitio, Nurita Dian Kestriani Saragi (Jurnal Kedokteran Meditek, 2025)
Introduction: Polyautoimmune involving multiple sclerosis (MS) and myasthenia gravis (MG) is rare, with overlapping clinical manifestations due to shared immunopathogenic mechanisms. The main challenge in such patients is the high risk of ventilator weaning failure, especially when complicated by ventilator-associated pneumonia (VAP). This report highlights the rarely reported success of ventilator weaning through a multidisciplinary and comprehensive management approach in MS-MG polyautoimmunity. Case Illustration: A 39-year-old female with relapsing-remitting MS and MG developed a myasthenic crisis requiring mechanical ventilation. Therapeutic plasma exchange (TPE) was initiated on the second day of treatment and continued for five cycles. Ventilator weaning was performed gradually in accordance with clinical improvement, but was hindered by VAP, necessitating tracheostomy. High-protein enteral nutrition support and early mobilization were initiated on the second day of treatment. After 24 days of intensive care, the patient was successfully weaned from the ventilator with stable respiratory function and improved muscle strength. She was discharged ten days later with tracheostomy care instructions and was able to perform independent active mobilization. Discussion: MS-MG polyautoimmunity presents complex immunological mechanisms that require a multidisciplinary approach. Evidence-based comprehensive management that integrates immunomodulatory therapy, treatment of VAP complications, high-protein enteral nutrition, mobilization, and progressive pulmonary rehabilitation significantly improved respiratory function and accelerated weaning from the ventilator. Conclusion: An evidence-based, comprehensive approach through multidisciplinary collaboration can enhance ventilator weaning and improve clinical outcomes and quality of life in patients with MS-MG polyautoimmunity.